Vessel wall imaging in COVID-19 associated carotid atherothrombosis and stroke: a case report and literature review - Md Noh, Mohamad Syafeeq Faeez; Yusof Khan, Abdul Hanif Khan; Mohd Sabri, Mohd Naqib; Kamis, Mohd Fandi Al-Khafiz; Mohd Yaakob, Mohd Naim; Abdul Rahim, Ezamin; Muda, Ahmad Sobri (Sage Publications Ltd., 2022)
COVID-19 associated neurological syndromes, including acute ischemic stroke, pose a challenge to treating physicians. The role of MRI in aiding diagnosis and further management is indispensable. The advent of new MRI sequences such as vessel wall imaging (VWI) allows an avenue in which these patients could be better investigated and treated. We describe our experience in managing a patient with COVID-19 associated atherothrombosis and stroke, focusing on the VWI imaging findings.